Generation and Analysis of Wire Rope Digital Radiographic Images; IOP Conference Series: Materials Science and Engineering; Vol. 132 : Modern Technologies for Non-Destructive Testing - Chakhlov S. V. Sergey Vladimirovich; Anpilogov P.; Batranin A. V. Andrey Viktorovich; Osipov S. P. Sergey Pavlovich; Zhumabekova Sh.; Yadrenkin I. (2016, 2016)
Title screen